2013
DOI: 10.1111/pan.12183
|View full text |Cite
|
Sign up to set email alerts
|

Robust closed‐loop control of induction and maintenance of propofol anesthesia in children

Abstract: A robust closed-loop system can provide effective propofol administration during induction and maintenance of anesthesia in children. Wide variation in the calculated Ce highlights the limitation of open-loop regimes based on pharmacokinetic/pharmacodynamic models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(58 citation statements)
references
References 24 publications
(56 reference statements)
0
58
0
Order By: Relevance
“…Results of a feasibility study in adults showed that this simple controller provided adequate anesthesia. This led to the development of a similar system for pediatric use, which resulted in the DOH within ten points of the target 89% of the time in a clinical study on 108 patients reported in [19] and [20]. Those results indicate that a robust PID controller manages relatively well with the significant interpatient uncertainty in a pediatric population.…”
Section: Closed-loop Control Of Depth Of Hypnosis In Intravenous Anesmentioning
confidence: 70%
“…Results of a feasibility study in adults showed that this simple controller provided adequate anesthesia. This led to the development of a similar system for pediatric use, which resulted in the DOH within ten points of the target 89% of the time in a clinical study on 108 patients reported in [19] and [20]. Those results indicate that a robust PID controller manages relatively well with the significant interpatient uncertainty in a pediatric population.…”
Section: Closed-loop Control Of Depth Of Hypnosis In Intravenous Anesmentioning
confidence: 70%
“…In children and adolescent patients, their closed-loop system outperformed skilled manual control of propofol and remifentanil [50]. Similarly, other research groups proved the consistently better performance of automated anaesthesia drug delivery compared with conventional manual control both in adults [51 & ,52] and children [53]. Although still not perfect, these closed-loop systems might assist the anaesthetist during difficult decision-making, certainly when the individual patient has a PK/PD profile that deviates from the typical patient as predicted by the population PK/PD model.…”
Section: Closed-loop Controlmentioning
confidence: 87%
“…The PK model and the first term of the PD model are considered linear studied on real patient data with the collaboration of anaesthesiologists and validated using blood samples provided by hospitals. [18,19,22]: ( 1 1 0 3 31 1 13 3 2 21 1 12 2 1 3 31 2 21 1 13 12 10 …”
Section: A Patient Modelmentioning
confidence: 99%
“…In this phase, typical disturbances can be applied additively to the output of the process to check the controller's ability to reject them [22]. A standard stimulus profile is defined and is presented in Fig 17. Each interval denotes a specific event in the operation theatre.…”
Section: B Maintenance Phasementioning
confidence: 99%